Boeing: surviving business turbulence after black swan cataclysms. Issue 1 (24th December 2021) - Gupta, Surabhi; Gupta, Nakul; Narayan, Shubham
Abstract : Theoretical basis: Capital structure theory. Research methodology: The case is meant for teaching and class discussion, and uses only secondary data based on published sources. The interpretation and perspectives presented are based solely on the secondary data. Case overview/synopsis: This paper aims to help current and future managers understand capital structure theory and the various equity and debt finance options available for raising capital. It also examines the financial analysis and strategic management of black swan events. After the class discussion, students will understand how to financially and strategically manage a company during black swan events and also have a deep dive into capital structure analysis of a large company. Complexity academic level: MBA/postgraduate/undergraduate courses on corporate finance or advanced corporate finance. Executive/management development programs and short duration Massive Open Online Courses on investment decision-making and advanced corporate finance. MBA/postgraduate/undergraduate courses on corporate strategy and economic environment and planning.